How sales managers can use salespeople's perceived attributes to monitor and motivate a sales force during relationship marketing - Saïd Echchakoui; Rachid Ghilal (European Research on Management and Business Economics (ERMBE), 2019)
This study uses the Markov chain and agency theory to demonstrate a link between a salesperson's perceived attributes with customer retention and both optimal effort and commission, using a relational perspective. The purpose is to show sales managers that, with a customer survey, they can use perceived sales force attributes to monitor and motivate employees during relationship marketing. This paper also demonstrates that optimal sales force compensation drives salespeople to enhance perceived attributes.
Keywords: M12; M31; M52; 650; Agency theory; Customer retention; Firm's financial value; Markov chain; Sales force